Does endometriosis have an effect on the survival of women with synchronous endometrial and ovarian cancer?. Issue 4 (December 2019) - Celik, Engin; Goksever Celik, Hale; Sozen, Hamdullah; Onder, Semen; Baktiroglu, Merve; Topuz, Samet; Salihoglu, Mehmet Yavuz
Purpose: Synchronous endometrial and ovarian cancer is defined as the concurrent presence of ovarian cancer with endometrial cancer. We aimed to evaluate whether there is an effect of endometriosis on progression-free survival and overall survival of women with synchronous endometrial and ovarian cancer. We also compared these findings with the patients having endometrial-only tumors and ovarian-only tumors. Methods: The patients who underwent surgery for endometrioid or clear-cell endometrial-only tumors and/or ovarian-only tumors and synchronous endometrial and ovarian cancer between 2005 and 2016 were included in this cohort study. The effect of the presence of endometriosis on progression-free survival and overall survival in these women who met the criteria was determined using statistical methods. Women were also compared regarding their demographic, clinical, and pathological characteristics. Results: A total of 176 patients were included in this study. All histology types of tumors located in endometrium or ovary were endometrioid or clear-cell cancer. Endometriosis was present in 62 patients (35.2%), whereas adenomyosis was present in 44 patients (25%). Endometriosis was diagnosed more frequently in women with ovarian-only tumors and synchronous endometrial and ovarian cancer than those with endometrial-only tumors (59.2% vs 5.7%, p < 0.001 and 45.7% vs 5.7%, p < 0.001, respectively). The patients with endometriosis showed no significantly longer progression-free survival and overall survival (hazard ratio = 1.70; 95% confidence interval = 0.48–6.03; p = 0.408 and hazard ratio = 1.67; 95% confidence interval = 0.30–9.44; p = 0.562, respectively). The presence of endometriosis was a stronger predictor for progression-free survival and overall survival comparing with the presence of adenomyosis. Conclusion: The women with synchronous endometrial and ovarian cancer should be informed that endometriosis has no detrimental effect on progression-free survival and overall survival.